Gift economies in the development of open source software: Anthropological reflections - Zeitlyn, D; Zeitlyn, D (Elsevier, 2003)
Building on Eric Raymond's work this article discusses the motivation and rewards that lead some software engineers to participate in the open source movement. It is suggested that software engineers in the open source movement may have sub-groupings which parallel kinship groups such as lineages. Within such groups gift giving is not necessarily or directly reciprocated, instead members work according to the 'axiom of kinship amity' - direct economic calculation is not appropriate within the group. What Bourdieu calls 'symbolic capital' can be used to understand how people work in order to enhance the reputation (of themselves and their group). © 2003 Elsevier Science B.V. All rights reserved.